Nas políticas de formação docente a continuidade de uma prática. Estudo de caso sobre programas de governo em Cáceres - Mato Grosso. - Lima, José Carlos de (Universidade do Vale do Rio dos Sinos, 2011)
This dissertation deals with the political education of teachers. The main objective is to consider proposals for teacher education in the State of Mato Grosso implemented by CEFAPRO, as well as the Syndicate of professional educators, and how they reach the schools of basic education. To consider proposals for training, used as theoretical support Frigotto (1996), Pepper (2002), Silva (2002) and others. Along the way, I was guided by the question: What perspective of a policy proposals for teacher training CEFAPRO implemented by the state of the union and the school provide teachers of Basic Education? To seek answers to this question, I have used the qualitative methodology in an interpretative perspective. The research subjects are three union leaders, three teachers trainers and three CEFAPRO educational coordinators of the selected schools. All subjects are teachers of Basic Education for Public Schools in the city of Cáceres - MT. Through contact with the union leadership, the CEFAPRO and selected schools, I collected data to construct a characterization of space research. Throughout a questionnaire, I collected and organized data for the characterization of the research subjects. Through semi-structured interviews, I sought to understand the concepts of the subjects on social categories, previously selected by means of theoretical study. They are: the State and political society, the state as civil society, social relations and class, the teacher as intellectual, teacher training proposal, the role of schools and democracy and citizenship. In support of these categories, it was used as theoretical support Gramsci (1979), (2000), Giroux (1997) Frigotto (1996), Silva (2002), Ferreira (1993) and others. One of the main methodological procedures that were used was the content analysis to analyze the transcripts of interviews. I sought the data in MEC proposals for teacher education developed in partnership with SEDUC / MT and the very SEDUC / MT, CEFAPRO of Educational Policy Project, the publicity materials for mobilization of the syndicate, as well as the minutes of the meetings. Looking for the data from the evaluative reports, referring to the 2006 academic year, we conducted data analysis comparing the respondents' opinions with the theoretical basis of each category. The analyses revealed that the political perspective that proposals for teacher education implemented in schools in Cáceres - MT contributes to the education to intervene in reality in order to construct another model of society.
Keywords: Estado; Educação; Sociedade; Escola; Formação política do professor; State; Education; Society; Teacher education policy; ACCNPQ::Ciências Humanas::Sociologia